2014
DOI: 10.1007/s13762-014-0729-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacteria by photocatalytic nano-TiO2 particles in the absence of light

Abstract: The potential eco-toxicity of fourteen different nanosized titanium dioxide (TiO 2 ) particles was studied using Gram-positive Bacillus subtilis and Gram-negative Escherichia coli (ATCC K12) as test organisms. These photosensitive nanoparticles (NPs) were found to be harmful to the organisms studied at different degrees; the antibacterial activity increased with primary particle size, reached the maximum level in the range of 16-20 nm, and then decreased as the primary particle size increased. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…An optimum NP concentration of 50 mg/L was employed in DLS measurements. It was also reported by others [ 35 , 36 , 37 ] and in our previous study [ 29 ] that at high NP concentrations, the particle size increased from one to two orders of magnitude immediately. As shown in Table 2 , the pHs were depicted between 6.5 and 8.2 at time 0, and 7.0 and 8.0 at time 72 h. The ionic strength of the test solutions was from 0.5 mM to 8 mM.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…An optimum NP concentration of 50 mg/L was employed in DLS measurements. It was also reported by others [ 35 , 36 , 37 ] and in our previous study [ 29 ] that at high NP concentrations, the particle size increased from one to two orders of magnitude immediately. As shown in Table 2 , the pHs were depicted between 6.5 and 8.2 at time 0, and 7.0 and 8.0 at time 72 h. The ionic strength of the test solutions was from 0.5 mM to 8 mM.…”
Section: Resultssupporting
confidence: 85%
“…Therefore, oxidative stress is documented as one of the main mechanisms of NP toxicity to organisms [ 17 , 22 , 23 , 24 , 25 , 26 ]. Some studies showed that photoreactive TiO 2 NPs can produce oxidative stress in dark conditions [ 27 , 28 , 29 ]. Metzler et al [ 16 , 17 ] observed growth inhibition of the green algae Pseudokirchneriella subcapitata exposed to TiO 2 NPs under fluorescence light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively few studies have dealt with the direct effects of TiO 2 NPs on bacteria. To date, most of the literature has focused on its photocatalytic applications under UV light (McCullagh et al 2007;Pigeot-Rémy et al 2011) and few studies have reported E. coli inactivation in the absence of light due to bacteria-TiO 2 NP interactions (Foster et al 2011;Swayamprava et al 2012;Zhukova et al 2012;Nesic et al 2014;Erdem et al 2014). A limited number of studies have shown the effects of particle size on bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the generation of reactive oxygen species (ROS) by TiO 2 NP photocatalysis 12 is commonly described as a key process that leads to cell surface alteration and cell viability loss 14 21 , 23 25 , 30 . However, the genericity of this mechanism is not supported by other reports on the harmful effects of TiO 2 NPs on bacteria in the absence of light 5 , 13 , 22 , 26 , 27 , and the lack of correlation between ROS production and the toxicity under UV illumination 29 . In addition, non-ROS-related toxicity has been reported for nanomaterials other than TiO 2 NPs but with similar photocatalytic properties such as ZnONPs 32 , 35 , MgONPs 31 , CeO 2 NPs 33 , and fullerenes 34 .…”
Section: Introductionmentioning
confidence: 78%